Contributions to the training of constructivist teachers: results in two countries - Solbes, Jordi; González, Eduardo Miguel (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The research has to do with the influence of participation in educational research on the quality of experimental science teachers’ teaching from Argentina and Spain. In order to know these teachers’ educational practice, a three-fold way was used: a questionnaire, a semi-structured interview, and class observation with six sections and 34 items. The research was carried out with 55 teachers from Spain and 23 from Argentine, and showed how, despite the differences both in teachers’ educational background and educational contexts in both countries, intensive didactic training and its implementation through research (whether in dissertations, master final theses, or other researches), favors a teaching practice with a wider constructivist orientation.